The C-Band All-Sky Survey (C-BASS): Simulated parametric fitting in single pixels in total intensity and polarization - Jew, L; Taylor, AC; Jones, ME; Barr, A; Chiang, HC; Dickinson, C; Grumitt, RDP; Harper, SE; Heilgendorff, HM; Hill-Valler, J; Jonas, JL; Leahy, JP; et al. (Oxford University Press, 2019)
The cosmic microwave background (CMB) B-mode signal is potentially weaker than the diffuse Galactic foregrounds over most of the sky at any frequency. A common method of separating the CMB from these foregrounds is via pixel-based parametric-model fitting. There are not currently enough all-sky maps to fit anything more than the most simple models of the sky. By simulating the emission in seven representative pixels, we demonstrate that the inclusion of a 5 GHz data point allows for more complex models of low-frequency foregrounds to be fitted than at present. It is shown that the inclusion of the C-BASS data will significantly reduce the uncertainties in a number of key parameters in the modelling of both the galactic foregrounds and the CMB. The extra data allow estimates of the synchrotron spectral index to be constrained much more strongly than is presently possible, with corresponding improvements in the accuracy of the recovery of the CMB amplitude. However, we show that to place good limits on models of the synchrotron spectral curvature will require additional low-frequency data.